(untitled) (Cuadernos de Análisis y Debate sobre Músicas Latinoamericanas Contemporáneas, 2020)
The analysis of Juan Campoverde’s work, exotic, focuses on the theme of the end of the nation as a priority, and moves towards what is called a certain historical nihilism. It shows the appearance of diverse temporalities in the work that would correspond with similar historical drifts, in such a way that we would be listening to those typical sequences of the times of late capitalism that the work expresses critically. Thus, it shows how late time passes without passing, stopped in the endless present of capitalism. In the face of this, we find in Campoverde an untimely time that is expressed in the temporal structures of the work.